N-glycosylation of recombinant therapeutic glycoproteins in plant systems - Balen, Biljana (Array, 2007)
Transgenic plants have recently emerged as a promising system for low-cost and large-scale production of therapeutic proteins. Despite many advantages plants offer as hosts for expression of recombinant proteins, there are certain limitations caused by major structural differences between plant and mammalian N-linked glycans. Thus, efforts are being made in order to eliminate, or at least minimize, plant-specific N-glycosylation as well as to supplement the plant endogenous system with human glycosyltransferases to obtain »humanized« non-immunogenic N-glycans on plant-made pharmaceuticals aimed for human therapy